NISTA MARRIAGE PRACTICES AT THE LOWEST MARRIAGE LEVEL URF PERSPECTIVE IN PEGAYAMAN SUKASADA VILLAGE, BULELENG, BALI - Tarik, Atika Agustina; Stiawan, Thoat; Ikhwanuddin, Mohammad (Universitas Islam Negeri Mataram, 2024)
The research method used in this research is qualitative research, a descriptive study type. The researcher uses qualitative research methods to obtain, study, and understand the phenomenon through in-depth data regarding the community's perspective on the practice of nista marriages in Pegayaman Village, Sukasada, Buleleng, Bali. This type of research uses descriptive research to explain and examine the phenomenon of nista marriages in Pegayaman Village from an 'Urf perspective. The researcher's data collection techniques are observation, documentation and interviews with informants from three categories, including other key informants from local community leaders, primary informants who are residents, and complementary informants who are migrants who live in the village and work in the village office. People in Bali use levels as identities according to their position, especially the Hindu population, which starts from the highest Brahmana, Ksatria, Waisya, and Sudra, the lowest caste. In contrast to the community in Pegayaman, where the majority of the population is Muslim, the level is implemented within the scope of marriage. Local traditions, empowerment, and community perceptions regarding nista marriages are the benchmarks for researchers analysing ancestral heritage from an Urf perspective. Binary opposition is used to explore the relationship between Islamic teachings and ancestral cultural heritage. The existence of 'Urf about Islamic teachings is the basis for the empirical facts of nista marriages in Pegayaman village. In studying the data obtained by researchers regarding slanderous marriages from the perspective of 'urf, it is limited to 'urf fasid, namely in nista marriages as the lowest level of marriage, which is contrary to the law and enriches the elements of family formation.